Comparing the bioequivalence and safety of liraglutide in healthy Chinese subjects: an open, single-dose, randomized, repeated, two-sequence, two-cycle phase I clinical trial. Issue 4 (3rd April 2023) - Xu, Zhongnan; Liu, Zhengzhi; Wang, Yanli; Xue, Jinling; Chang, Tianying; Cui, Yingzi; Cheng, Yang; Liu, Guangwen; Wang, Wanhua; Zhou, Yannan; Yu, Shuang; Ren, Qing; et al.
ABSTRACT: Background: Glucagon-like peptide-1 (GLP-1) is an endogenous incretin hormone. Liraglutide, a GLP-1 receptor agonist, can lower blood sugar by increasing insulin production and inhibiting the production of glucagon. This study researched the bioequivalence and safety of the test and reference drugs in healthy Chinese subjects. Research design and methods: Subjects (N = 28) were randomly divided into group A and group B at a ratio of 1:1 for a two-cycle cross-over study. There was single dose per cycle with subcutaneous injection of the test and reference drugs, respectively. The washout was set at 14 days. Plasma drug concentrations were detected by specific liquid chromatography and tandem mass spectrometry (LC-MS/MS) assays. Statistical analysis of major pharmacokinetic (PK) parameters was conducted to assess drug bioequivalence. In addition, we evaluated the safety of the drugs throughout the trial. Results: The geometric mean ratios (GMRs) of Cmax, AUC0-t, and AUC0-∞ for the test and reference drugs were 107.11%, 106.56%, 106.09%, respectively. The 90% confidence intervals (CIs) were all within 80%-125%, meeting the bioequivalence standards. In addition, both had good safety in this study. Conclusion: The study shows that the two drugs had similar bioequivalence and safety. Clinical trial registration: DCTR: CTR20190914; ClinicalTrials.gov: NCT05029076